Peak nasal inspiratory flow evaluation as an objective method of measuring nasal airflow - Teixeira,Rodrigo Ubiratan Franco (2011)
Acoustic rhinometry, rhinomanometry and Inspiratory Peak Nasal Flow (IPNF) are used in order to objectively assess nasal patency. These are expensive not very practical tests, except for IPNF, which is a fast, simple and low cost method. OBJECTIVE: To assess IPNF in healthy individuals complaining of nose obstruction caused by allergic rhinitis. METHOD: IPNF use in 78 individuals with and without rhinitis symptoms. STUDY DESIGN: Contemporary cross-sectional cohort. RESULTS: IPNF showed significant results for nasal obstruction, rhinorrhea, pruritus, sneezes and tearing (p < 0. 001). There was no correlation between the presence of nasal septum deviation and IPNF (p = 0. 561). We found a positive correlation between IPNF and the Visual Analogue Scale (VAS) for nasal obstruction (p = 0. 002). In the multiple linear regression model, there was a statistical significance between the values found in IPNF with allergic rhinitis and age (p = 0. 005 and p = 0. 023 respectively). CONCLUSIONS: IPNF proved to be a reliable method to detect changes in nasal patency, by obstructive causes as well as inflammatory causes, with an acceptable level of statistical significance, simple, easy to handle, inexpensive and reproducible